APPLICATION OF AI IN EVERYDAY LIFE - K. Sharma, Pramod; Chaturvedi, Poonam; Raja, Iltaf; Sahal, Harsh (International Journal of Psychosocial Rehabilitation, 2020)
This review paper comes up with an overview of the role of AI in everyday life. As AI has become a vital role in everyday life, transforming the way we work and communicate. This abstract explores the impact of AI on our daily lives. Emphasizing its presence in various sectors such as education, entertainment, transportation, and healthcare. AI also plays a vital role in healthcare by early detection of disease and helping to recover patient care. This paper helps us to highlight the role of AI in everyday life. AI in everyday life is not just a technological advancement but a societal shift that needs thoughtful consideration and ethical guidance.